2014
DOI: 10.1007/s00280-014-2403-2
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of afatinib, an irreversible ErbB family blocker, in patients with various solid tumors

Abstract: This population pharmacokinetic model adequately described the pharmacokinetics of afatinib in different cancer patient populations and therefore can be used for simulations exploring covariate effects and possible dose adaptations. The effect size for each of the individual covariates is not considered clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 19 publications
9
48
2
1
Order By: Relevance
“…The current analysis showing that mild and moderate hepatic impairment had no obvious effect on the pharmacokinetics of a single afatinib dose is consistent with data from a population pharmacokinetic analysis of patients with advanced solid tumours receiving continuous doses of afatinib [18]. In this analysis, hepatic impairment, either based on individual clinical laboratory tests (alanine transaminase, aspartate transaminase and bilirubin) or a composite liver dysfunction measure, had no significant influence on afatinib exposure.…”
Section: Discussionsupporting
confidence: 87%
“…The current analysis showing that mild and moderate hepatic impairment had no obvious effect on the pharmacokinetics of a single afatinib dose is consistent with data from a population pharmacokinetic analysis of patients with advanced solid tumours receiving continuous doses of afatinib [18]. In this analysis, hepatic impairment, either based on individual clinical laboratory tests (alanine transaminase, aspartate transaminase and bilirubin) or a composite liver dysfunction measure, had no significant influence on afatinib exposure.…”
Section: Discussionsupporting
confidence: 87%
“…This might be partially explained by increased afatinib plasma exposure in these patients, as gender and body weight were previously identified as covariates for exposure [18]. In line with this, pharmacokinetic analyses suggested that dose reductions tended to occur in patients who had higher initial afatinib plasma concentrations, with tolerability-guided dose modification reducing excessive afatinib exposure.…”
Section: Efficacysupporting
confidence: 57%
“…The afatinib concentrations required for those effects are lower than the maximal plasma concentrations reported in patients of one study [42]. However, lower maximal concentrations have been reported in other studies [43][44][45][46][47][48][49][50] and the vast majority of patients are probably not going to reach afatinib plasma levels of 1000 ng/ml and above and are therefore not prone to develop the effects analyzed in this paper. Nevertheless, those high concentrations could be reached following accidental overexposure to afatinib.…”
Section: Discussioncontrasting
confidence: 43%